The need to apply the overall quality intellectual foundation in the university education system" between performance challenges and the university student’s perspective (Field study on a sample of -Msila University students) - laadjal, afifa (Journal of Social Sciences and Humanities, 2023)
This research paper aims to limit the intellectual foundations of comprehensive quality in university education by seeking the need to apply total quality management by studying students' attitudes and their opinion on these proposed principles and foundations To achieve these goals an analytical descriptive approach was used and a questionnaire form was applied to A sample of (50) students from -Msila University and after collecting data and analyzing it statistically, the results showed in the first order that there is a preparation for the educational and organizational climate in the university as there is a fit for programs and curricula with the goals of the university and the labor market as the extent of the investigation is evaluated Pass to the goals of teaching performance of university education with the inventory of some of the constraints that limit the application of total quality gas at the University where he supported these findings to review some of the recommendations and principles of the proposals.